Current standards of physical growth and development (height and weight) in infancy - L.V. Sahno; M.O. Revnova; I.V. Koltunceva; T.V. Mishkina; I.M. Gajduk; S.V. Bairova (LCC «Medicine-Inform», 2019)
L.V. Sahno, M.O. Revnova, I.V. Koltunceva, T.V. Mishkina, I.M. Gajduk, S.V. Bairova St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation Background: evaluation of the rate of physical growth and development is required for the quality assessment of health of any given child. Dynamic growth monitoring provides early diagnosis of pathologies and therapeutic measures. Acceleration, environmental externalities, and regional specificities affect physical development thereby resulting in the disproportional growth. Therefore, regular reviewing of physical development standards considering regional specificities and evolving parameters of physical growth and development is required. In daily pediatric practice, centile tables developed by Prof. I.M. Vorontsov (1986) are commonly used. Aim: to compare growth parameters (height and weight) of infants aged 0-12 months born in 2016-2017 and I.M. Vorontsov data (1986). Patients and Methods: 2419 full-term infants born in 2016-2017 were examined. Height and weight centiles, expected value (mean, M) and standard deviation were calculated using Microsof t Excel software. Results: weight and height tend to be greater both in boys and girls born in 2016-2017 as compared with infants born in 1986. Conclusion: dynamic growth monitoring of any given child is required. Outpatient electronic health records should be used to evaluate the effect of climatic, social economic and ethnical factors on physical development (in particular, considering potential digitalization of Russian medicine). Software should include all-Russian automated analysis and construction of growth charts or plots based on the statistical data from certain regions and country in whole for every 5 to 10 years. Keywords: physical growth and development, centile charts, child, weight, height (length), mass-growth indicators, dynamic monitoring. For citation: Sahno L.V., Revnova M.O., Koltunceva I.V. et al. Current standards of physical growth and development (height and weight) in infancy. Russian Journal of Woman and Child Health. 2019;2(4):331-336.